2018
DOI: 10.1080/10903127.2017.1408728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telestroke on Thrombolysis Times and Outcomes: A Meta-analysis

Abstract: Telestroke significantly reduced OTD and hospital stay durations in stroke patients without increasing the risk of mortality or sICH. Therefore, telemedicine can improve stroke care in regional areas with minor experience in thrombolysis. Further randomized controlled trials are needed to assess the benefits of telestroke systems, especially in terms of cost-effectiveness and quality of life outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 43 publications
3
74
0
1
Order By: Relevance
“…Similar findings have been reported in the US and Canada . In a meta‐analysis of 26 studies (6605 patients receiving thrombolysis), no significant differences were found between stroke telemedicine and control groups in terms of in‐hospital mortality, 90‐day mortality, symptomatic intracranial haemorrhage, and clinical outcome at discharge or at 90‐day follow‐up …”
Section: Discussionsupporting
confidence: 83%
“…Similar findings have been reported in the US and Canada . In a meta‐analysis of 26 studies (6605 patients receiving thrombolysis), no significant differences were found between stroke telemedicine and control groups in terms of in‐hospital mortality, 90‐day mortality, symptomatic intracranial haemorrhage, and clinical outcome at discharge or at 90‐day follow‐up …”
Section: Discussionsupporting
confidence: 83%
“…Therefore, hybrid models were developed to provide a partially outpatient and partially telemonitored, home-based CR programme [11]. This has been reinforced by the recent successes of telemedicine in several emergency and rehabilitation indications [27][28][29]. In this study, we aimed to provide class I evidence regarding the comparability of hybrid CR models to the standard CR programmes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that only 1-8% of stroke patients receive proper treatment and the others face poor outcomes due to delayed referral [3][4][5][6]. Therefore, prompt action is needed to identify patients with stroke as soon as possible, even in the pre-hospital stage [7]. Although public education at the community level plays an undeniable role in promptly calling emergency medical services (EMS) after a stroke, effective interventions in the healthcare system begin the moment a patient or his/her companion contacts EMS.…”
Section: Introductionmentioning
confidence: 99%